1998
DOI: 10.1002/hep.510270106
|View full text |Cite
|
Sign up to set email alerts
|

Q-T interval prolongation in cirrhosis: Prevalence, relationship with severity, and etiology of the disease and possible pathogenetic factors

Abstract: Prolonged Q-T interval predicts severe arrhythmias and sudden death, and has been shown to occur in alcoholic liver disease and cirrhotic patients who are candidates for liver transplantation. This study first evaluated the prevalence of prolonged Q-T interval in a large population of unselected patients with cirrhosis, and assessed the relationship between abnormal Q-T, etiology, and severity of liver disease and mortality of patients. Possible causes of Q-T abnormality were also explored. Ninety-four patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
321
5
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 334 publications
(373 citation statements)
references
References 34 publications
28
321
5
7
Order By: Relevance
“…Few years later, human studies in nonalcoholic cirrhosis showed similar results. Bernardi et al [12] measured systolic time intervals that has been validated as a reliable method of assessing ventricular contractile performance [20] and found the ratio of pre-ejection period to left ventricular ejection time to be prolonged in 22 alcoholic and nonalcoholic cirrhotic patients both at rest and after exercise, an indication of contractile dysfunction. Grose et al [21] reported a submaximal increase in cardiac output following exercise in both alcoholic and nonalcoholic cirrhotic patients compared with controls.…”
Section: Systolic Dysfunctionmentioning
confidence: 99%
See 3 more Smart Citations
“…Few years later, human studies in nonalcoholic cirrhosis showed similar results. Bernardi et al [12] measured systolic time intervals that has been validated as a reliable method of assessing ventricular contractile performance [20] and found the ratio of pre-ejection period to left ventricular ejection time to be prolonged in 22 alcoholic and nonalcoholic cirrhotic patients both at rest and after exercise, an indication of contractile dysfunction. Grose et al [21] reported a submaximal increase in cardiac output following exercise in both alcoholic and nonalcoholic cirrhotic patients compared with controls.…”
Section: Systolic Dysfunctionmentioning
confidence: 99%
“…Its prevalence is about 45%, which is strikingly higher than the 5% prevalence in the general population, and is broadly proportional to the severity of cirrhosis, rising from 25% in class A to 51% in class B and up to 60% or more in class C of Child-Pugh classification [12]. The presence of prolonged QT interval provides the substrate for ventricular arrhythmias and therefore may be responsible for the sudden deaths observed following stressful procedures such as TIPS insertion or liver transplantation.…”
Section: Electrophysiological Abnormalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperdinamic circulation [3], QTc prolongation [4,5], beta-receptors desensitization [6,7], reduced systolic competence under strains [8][9][10][11] and diastolic dysfunction [12][13][14][15][16][17] are the key features of cirrhotic cardiomyopathy. Diastolic dysfunction, characterized by an altered pattern of transmitral flow due to impaired diastolic relaxation of left ventricle, can be easily assessed by echocardiography and accordingly can be considered as a marker of this condition.…”
Section: Introductionmentioning
confidence: 99%